2018
DOI: 10.1101/329375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Discovery of the Functional Impact of Somatic Genome Alterations in Individual Tumors through Tumor-specific Causal Inference

Abstract: We report a tumor-specific causal inference (TCI) framework, which discovers causative somatic genome alterations (SGAs) through inferring causal relationships between SGAs and molecular phenotypes (e.g., transcriptomic, proteomic, or metabolomic changes) within an individual tumor. We applied the TCI algorithm to tumors from The Cancer Genome Atlas (TCGA) and identified those SGAs that causally regulate the differentially expressed genes (DEGs) within each tumor. Overall, TCI identified 634 SGAs that cause ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…27 A previous study established that NEFH is a cancer driver because of its functional impact on KRAS and MTORC1 signaling. 28 We conducted survival analyses of LUAD patients with the EGFR 19Del/L858R mutation or EML4-ALK fusion in the TCGA dataset; our findings suggested that patients with high NEFH expression had worse prognoses than patients with low NEFH expression (Figure 3(d,e)). Survival analyses of patients with EGFR or ALK mutations in the Pan-Cancer dataset confirmed that NEFH was a cancer-promoting factor (Supplementary Figure 2(a,b)).…”
Section: Somatic Mutational Landscape Between Pre-treatment and Post-treatment Samplesmentioning
confidence: 90%
“…27 A previous study established that NEFH is a cancer driver because of its functional impact on KRAS and MTORC1 signaling. 28 We conducted survival analyses of LUAD patients with the EGFR 19Del/L858R mutation or EML4-ALK fusion in the TCGA dataset; our findings suggested that patients with high NEFH expression had worse prognoses than patients with low NEFH expression (Figure 3(d,e)). Survival analyses of patients with EGFR or ALK mutations in the Pan-Cancer dataset confirmed that NEFH was a cancer-promoting factor (Supplementary Figure 2(a,b)).…”
Section: Somatic Mutational Landscape Between Pre-treatment and Post-treatment Samplesmentioning
confidence: 90%
“…The major objective in (Cai et al, 2019) is to identify driver genes by estimating likely causal relationships between somatic genomic alterations and genes which are differentially expressed relative to normal. Bayesian inference is applied to each individual tumor sample to associate differential expression with a set of genomic alterations in the sample.…”
Section: Heterogeneitymentioning
confidence: 99%
“…Whereas this program bears similarities with ours the objectives and methodology are quite different: our analysis is top-down, based on applying a known network to directly characterize a tumor population with a relatively concise set of paired genomic-transcriptomic relationships, and designed for quantification of inter-tumor heterogeneity. In contrast, the approach in (Cai et al, 2019) is model-driven and the networks are learned.…”
Section: Heterogeneitymentioning
confidence: 99%
“…To better understand cancer heterogeneity, large-scale cancer genomics projects, such as the Cancer Genome Atlas (TCGA), the International Cancer Genome project, and the Memorial Sloan Kettering-Integrated Mutation Profiling project have systematically profiled thousands of tumors, holding the promise to realize personalized treatment [3][4][5][6]. Among the collected genome-scale omics data, somatic mutation profiles have been used to discover causal drivers of tumors [7][8][9][10][11][12][13] and further reveal informative cancer subtypes [14,15]. In pursuit of this vision, computational approaches have been developed to stratify tumors according to high-dimensional, noisy and sparse somatic mutation profiles [1,[16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%